An Investigation into the Learning Difficulties Experienced by Indian School Children In Learning Division Algorithm of Simple Fractions - MAITI, TAPAN KUMAR; METE, JAYANTA KUMAR (SCHOOL SCIENCE, 2006)
He only division algorithm for simple fractions which is being taught to the school children is the reciprocal algorithm. Apparently it is very simple. But, taught mechanically, it gives rise to many learning difficulties, which the present investigation intends to highlight for the benefit of students, teachers and method masters.